PERAN PENDIDIKAN DAN PELATIHAN DALAM MEMODERASI PENGARUH SISTEM KOMPUTERISASI DAN KOMPETENSI PENGGUNA PADA KINERJA SIA - Ariyanatha, I Gusti Ngurah; Suardana, Ketut Alit (Buletin Studi Ekonomi; VOL.24.NO.1.FEBRUARI 2019, 2019)
Abstract: The Role of Education and Training in Moderating the Effects of Computerized Systems and User Competence on SIA Performance. Revenue Agency has an important and strategic role to increase regional income in Bali Province. Therefore, it needs to be supported by an effective and efficient accounting information system. The purpose of this study was to obtain empirical evidence of the influence of computerized systems and user competencies on the performance of accounting information systems and to obtain empirical evidence of the role of education and training in moderating the influence of computerized systems and user competencies on the performance of accounting information systems at Bapenda in Bali Province. The population in this study were all SIA users in Bapenda, Bali Province. The method of determining the sample using a saturated sampling technique, so that the entire population of 42 employees is used as the research sample. The analysis technique used is Moderated Regression Analysis (MRA).